Enzymatic glucose biosensor based on ZnO nanorod array grown by hydrothermal decomposition - Lei, Y. (2011)
We report herein a glucose biosensor based on glucose oxidase (GOx) immobilized on ZnO nanorod array grown by hydrothermal decomposition. In a phosphate buffer solution with a pH value of 7.4, negatively charged GOx was immobilized on positively charged ZnO nanorods through electrostatic interaction. At an applied potential of +0.8 V versus Ag/AgCl reference electrode, ZnO nanorods based biosensor presented a high and reproducible sensitivity of 23.1 μA cm−2 mM−1 with a response time of less than 5 s. The biosensor shows a linear range from 0.01 to 3.45 mM and an experiment limit of detection of 0.01 mM. An apparent Michaelis-Menten constant of 2.9 mM shows a high affinity between glucose and GOx immobilized on ZnO nanorods.